Nutrition Risk Assessment Using the Modified NUTRIC Score in Cirrhotic Patients with Acute Gastroesophageal Variceal Bleeding: Prevalence of High Nutrition Risk and its Independent Prognostic Value - Tsai, Ming-Hung (Nutrients, 2019)
Malnutrition is associated with adverse outcomes in patients with liver cirrhosis. Relevant data about nutrition risk in critically ill cirrhotic patients are lacking. The modified Nutrition Risk in Critically Ill (mNUTRIC) score is a novel nutrition risk assessment tool specific for intensive care unit (ICU) patients. This retrospective study was conducted to evaluate the prevalence and prognostic significance of nutrition risk in cirrhotic patients with acute gastroesophageal variceal bleeding (GEVB) using mNUTRIC scores computed on admission to the intensive care unit. The major outcome was 6-week mortality. One-hundred-and-thirty-one admissions in 120 patients were analyzed. Thirty-eight percent of cirrhotic patients with acute GEVB were categorized as being at high nutrition risk (a mNUTRIC score of ≥5). There was a significantly progressive increase in mortality associated with the mNUTRIC score (χ(2) for trend, p < 0.001). By using the area under a receiver operating characteristic (ROC) curve, the mNUTRIC demonstrated good discriminative power to predict 6-week mortality (AUROC 0.859). In multivariate analysis, the mNUTRIC score was an independent factor associated with 6-week mortality. In conclusion, the mNUTRIC score can serve as a tool to assess nutrition risk in cirrhotic patients with acute GEVB.